The Role of Physical Activity in Strengthening the Immune System (Open Herald: Periodical of Methodical Research, 2024)
Physical activity plays a significant role in enhancing the body's immune function, thereby reducing the risk of infections and promoting overall health. This article explores the multifaceted relationship between physical activity and the immune system, examining the various mechanisms through which exercise strengthens immune function. From boosting the production of immune cells to enhancing immune surveillance and reducing inflammation, regular physical activity has been shown to confer numerous benefits to immune health. The article synthesizes current research findings and practical insights to highlight the importance of incorporating physical activity into daily routines to support immune resilience and reduce susceptibility to infectious diseases